METAPHORICAL CONCEPTUALIZATION OF EMOTIONS IN TYPOLOGICALLY DIFFERENT LANGUAGES: INSIGHTS FROM CONTEMPORARY PSYCHOLOGY (International Conference on Educational Discoveries and Humanities, 2025)
The deep relationship between language and thought has always attracted researchers. In particular, on the basis of the fields of modern psychology and Linguistics, there is a special connection between emotions and their expression through language, between the categories that are formed in our minds and their metaphorical concept. Emotions are expressed in each language in their own way: their forms of expression, symbolic manifestations, and reflection in the mind are closely related to the culture, mentality, and psychological worldview of society. Under the influence of the directions of modern psychology, the role of linguistic and cognitive approaches in the perception and interpretation of emotions is increasing. Each language owner enriches speech activity with the help of various metaphorical concepts that cover his emotional experiences, manifest a system of knowledge about the world.